High efficiency 2.4 GHz CMOS two stages class-F power amplifier for wireless transmitters - Murad, S.A.Z.; Md Isa, M.N.; Bakar, F.A.; Sapawi, R. (Bentham Science Publishers B.V., 2016)
A design of CMOS class-F power amplifier (PA) at 2.4-GHz for wireless transmitters is presented. The class-F PA design is implemented by using 0.13-μm CMOS process. The proposed class-F PA employs cascade topology. The transistor’s on resistance is decreased by designing the transistors in parallel. Therefore, the efficiency is increased. The first stage is a common-source driver stage is biased in a class-AB to provide sufficient input voltage swing for the amplifier stage, while the amplifier stage is biased in cut-off region. Therefore, the transistor can operate as a switching-mode for high efficiency. The simulation results show that the power added efficiency (PAE) of 60% is obtained at 1.3 V power supply and the PA delivers 12 dBm output power. The chip area is 0.66 mm2.